Palliative care for cancer patients in a primary health care setting: Bereaved relatives' experience, a qualitative group interview study - Neergaard, Mette Asbjoern (BioMed Central, 2008)
BACKGROUND: Knowledge about the quality and organisation of care to terminally ill cancer patients with a relatives' view in a primary health care setting is limited. The aim of the study is to analyse experiences and preferences of bereaved relatives to terminally ill cancer patients in a primary care setting to explore barriers and facilitators for delivery of good palliative home care. METHODS: Three focus group interviews with fourteen bereaved relatives in Aarhus County, Denmark. RESULTS: Three main categories of experience were identified: 1) The health professionals' management, where a need to optimize was found. 2) Shared care, which was lacking. 3) The relatives' role, which needs an extra focus. CONCLUSION: Relatives experience insufficient palliative care mainly due to organizational and cultural problems among professionals. Palliative care in primary care in general needs improvement and attention should be drawn to the "professionalization" of the relatives and the need to strike a balance between their needs, wishes and resources in end-of-life care and bereavement.